Optimization of Safety and Reliability of Electrical Systems of Tourist Ships in Labuan Bajo through FMEA - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah; Pramana, Putu Indra (Department of Naval Architecture - Diponegoro University, 2025)
This study aims to optimize the safety and reliability of the electrical systems on tourist ships in Labuan Bajo through Failure Mode and Effects Analysis (FMEA). The analysis identified key electrical components, including the battery and energy storage system, electric generator, charging system, and cables and connectors, as having high Risk Priority Numbers (RPNs). These components, if they fail, could significantly impact ship operations and passenger safety. The study emphasizes the importance of regular maintenance and early detection to prevent system failures and highlights critical areas, such as backup energy storage and power distribution, that require more attention. Despite having lower RPNs, components like the ship's lighting system and ventilation system still require maintenance to ensure smooth operation and passenger comfort. Additionally, the research revealed that proper load management of the electric generator is essential for extending its lifespan. It is recommended to limit the generator load to 60-86% of its maximum capacity to reduce the risk of overheating and enhance operational efficiency. By implementing these preventive measures, ship operators can enhance the reliability and safety of the electrical systems, leading to a safer and more comfortable experience for tourists while minimizing disruptions to operations. Overall, the findings show that FMEA is a valuable tool for optimizing the electrical systems of tourist ships, ensuring they operate with maximum efficiency and minimum risk.